Digital Transformation and Its Implications for Commercial Law Practice in Indonesia - Sulistya Eviningrum; Nizam Zakka Arrizal; Asa Barno Happy Ramadhany; Yudita Ayu Widya Perdana (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Abstract Introduction to the Problem: the urgency of this research is that there’s so many challenge and major changes due to digital transformation in commercial law practice in Indonesia, Introducing new difficulties and opportunities in the field of electronic transactions, digital consumer protection, and intellectual property rights. This study explores fundamental changes in the legal structure and mechanisms needed to accommodate evolving digital business models. Purpose/Study Objectives: The Purpose of this study are to explore the dynamics of digital transformation in the context of Indonesian commercial law, focusing on three key aspects: mechanisms for changing legal practices, regulatory challenges, and strategies for adapting the legal framework to digital innovation. Design/Methodology/Approach: This piece of writing relies on normative law research. The statutory and conceptual approach models were applied. Findings: The findings indicate that although regulations have attempted to keep pace with technological developments, there is still a need for improvement in terms of transaction security, electronic legal proof, and personal data protection. The study's findings are expected to provide policymakers with recommendations for developing policies that are responsive and adaptive to the digital age.. Paper Type: Research Article.